Historical disputes over the Second World War and its consequences in the context of relations between the European Union and Russia - Teteyan, Arshaluys (History and Culture, 2023)
The aim of the study is to analyze the role and the place of the ˝Politics of memory˝ in the context of relations between Russia and European Union. Who won World War II ?, what was the role of the second front ?, the actions of the Red Army in the countries of Eastern and Central Europe and many other problems always had been the apple of discord between Russian and Western historians. Over the past decades, these problems have become an integral part of the already tense relations between Russia and European countries. These problems have the important role in the context of Russian-European Union relations. Over the past decades, European organizations EU and the Council of Europe have adopted several resolutions that provoked a mixed reaction in Russia.In the framework of this work, historical discussions between Russia and the EU are considered in the context of the Eastern policy of the EU, in particular after the implementation of the European Neighborhood Policy and Eastern Partnership programs.
Keywords: European Parliament; retelling of history; rethinking history; «Politics of memory»; Second world war; «Memory Wars»; Munich Agreement; Ribbentrop-Molotov Pact